2017
DOI: 10.11118/actaun201765061967
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Behaviour on Slovak Yoghurt and Fermented Milk Products Market

Abstract: Brunensis, 65(6): 1967Brunensis, 65(6): -1978 Milk and dairy products present an important source of essential nutrients which should be a part of human beings nutrition. While the recommended consumption of milk and dairy products is set at the level of 220 kg/person/year, the current studies show that Slovaks consume only 160 kg/person/year. One of the possibilities how to reverse this negative trend is to raise the Slovak consumers awareness of the positive impacts of yoghurts and fermented milk products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…After the Slovak Republic joined the EU, milk quota was allocated for milk production, which was set at the level of 1,061.6 mil.kg in 2009/2010 (Kubicová, 2012) and further increased to the level of 1,115.6 mil.kg in 2014/2015 (Kubicová, 2014); and after five years of a preparatory increase in their level, milk quotas disappeared on April 1 th 2015 (Eurostat, 2015). Nowadays trend shows, that the of milk and dairy products consumption declines (Košičiarová et al, 2017).As presented in the part Results and discussion, the current consumption of milk and dairy products in the Slovak Republic is about 174 kg per person per year, which represents lower consumption by 20% compared to the recommended intake (Kubicová et al, 2019).…”
Section: Introductionmentioning
confidence: 92%
“…After the Slovak Republic joined the EU, milk quota was allocated for milk production, which was set at the level of 1,061.6 mil.kg in 2009/2010 (Kubicová, 2012) and further increased to the level of 1,115.6 mil.kg in 2014/2015 (Kubicová, 2014); and after five years of a preparatory increase in their level, milk quotas disappeared on April 1 th 2015 (Eurostat, 2015). Nowadays trend shows, that the of milk and dairy products consumption declines (Košičiarová et al, 2017).As presented in the part Results and discussion, the current consumption of milk and dairy products in the Slovak Republic is about 174 kg per person per year, which represents lower consumption by 20% compared to the recommended intake (Kubicová et al, 2019).…”
Section: Introductionmentioning
confidence: 92%
“…The obtained results are similar to those in Italy, where supermarkets and specialty stores were the most common channels for organic food purchase (Gambelli et al, 2003). A survey conducted in Slovakia found that most respondents (44.8 %) prefer to buy yoghurt and other fermented dairy products in the hypermarket or supermarket (Košičiarová et al, 2017). Only a small number of respondents buy organic yoghurt in local stores (N = 33), at fairs (N = 18) or directly from producers (N = 31) Table 3.…”
Section: Behaviour In Organic Yoghurt Purchase and Consumptionmentioning
confidence: 99%
“…Although organic dairy products, along with fresh fruits and vegetables, are the most popular products in the EU organic food market, there are few international studies examining consumer preferences and behaviour in buying and consuming yoghurt. Some studies have examined the satisfaction of customers who buy yoghurt (Wantasenet et al, 2017), or consumers behaviour in buying and consuming yoghurt (Košičiarová et al, 2017;Raza et al, 2020). Hlédik and Lógó (2017) explored product experiences and consumer preferences regard to selection of a yoghurt brand.…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of milk and dairy products has positive health effects for people (Košičiarová et al, 2017), which are mainly related to the development of the brain and nervous tissues. In the context of a brief overview, the irreplaceable position of milk and dairy products in human nutrition can be deduced.…”
Section: Introductionmentioning
confidence: 99%